Ethical considerations relating to healthcare resource allocation decisions. Issue 11 (11th November 2019) - Olver, Ian; Dodds, Susan; Kenner, Jeremy; Kerridge, Ian; McGovern, Kevin; Milligan, Eleanor; Mortimer, Robin; ,
Abstract: Public policy decisions about patients' access to limited healthcare resources must be defensible and responsive to the interests of those affected. Decision‐makers should articulate their reasoning and recommendations so that citizens can judge them. While the context of policy decisions will differ, their legitimacy depends upon the transparency of the reasoning, the accountability of the decision‐makers, the testability of the evidence used to inform the decision‐making and the inclusive recognition of those the decision affects. An example of applying this framework to resource allocation is that of approving effective high‐cost anticancer drugs in a timely fashion.